MtDNA-Based Phylogeography of the Red Alga Agarophyton vermiculophyllum (Gigartinales, Rhodophyta) in the Native Northwest Pacific - Zhong, Kai-Le; Song, Xiao-Han; Choi, Han-Gil; Satoshi, Shimada; Weinberger, Florian; Draisma, Stefano G. A.; Duan, De-Lin; Hu, Zi-Min (Frontiers in Marine Science, 2020)
The repeated transgression and regression of coastlines mediated by the late Quaternary glacial-interglacial cycles make the northwest Pacific to become a hotspot to study marine speciation and population diversity. The red alga Agarophyton vermiculophyllum is an ecologically important foundation species native to the northwest Pacific, capturing considerable research interest due to its range-wide invasiveness in Europe and North America. However, the knowledge of phylogeographic structure and intraspecific genetic diversity across the entire native range are still scarce. Here, we used 1214-bp of mitochondrial cytochrome c oxidase subunit 1 (cox1) to explore phylogeographic patterns, lineage structure and population genetic differentiation of 47 A. vermiculophyllum populations in the northwest Pacific. Our DNA data revealed overall high haplotype diversity and low nucleotide diversity, and five phylogeographically structured genetic lineages that diverged significantly from each other. S-DIVA analyses showed the ancestors of A. vermiculophyllum originating from multiple areas encompassing the Japan-Pacific coast, the Sea of Japan, East and South China Seas. These combined evidence indicate that A. vermiculophyllum might have survived in multiple scattered glacial refugia during the late Quaternary climate oscillations in the northwest Pacific. This knowledge may help to better understand how climate shifts interacted with contemporary environments to contribute to intraspecific genetic variation and adaptation capability of seaweed under current global climate warming.